Relationship Between Vitamin A and Fat Intake, with Growth Retardation. Villa Maria del Triunfo, Lima – Peru - Guerra Cossio, Vladimir (1999)
OBJETIVE: To evaluate the relationship between Vitamin A and fat intake, with growth retardation (GR) among 12- to 47-months-old children. METHODS: A prospective, analytic study on 70 children from "Las Torres de Melgar", Villa Maria del Triunfo, Lima–Peru. Vitamin A and fat intake were assessed through self-reported remind intake, and usual intake through the IVACG method. Growth was measured by anthropometric evaluations. RESULTS: We found GR in 27,22%; inadequate amounts of Vitamin A intake (IAVAI) in 54,3%, and inadequate amounts of fat intake in 87%. Finally, 24,3% of them have a fat intake lower than 10 g/d, which is insufficient for Vitamin A absorption). CONCLUSION: IAVAI correlates significantly with GR (p<0,01) among our studied people.